1980
DOI: 10.1002/jso.2930140409
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides associated with florid sarcoid reactions

Abstract: We report a 59-year-old woman with disease manifestations diagnosed as mycosis fungoides (MF), as well as findings of sarcoidosis. The concurrence of these two disorders, both of which may be associated with basic immunopathogenic factors, has been reported. Histologically, the cutaneous findings of both non-caseating granulomas and an infiltrate compatible with MF in the same site leads to a discussion of granulomatous MF. Whether granulomatous MF simply represents sarcoidosis developing concomitantly with MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The percentage of patients with unfavorable outcome is identical to that in the study by Chen et al, 13 who reported death due to the disease in 40% of patients with GMF. Whereas the occurrence of granulomas in MF has been considered to be associated with a favorable prognosis by some authors, 6,18 other investigators could not confirm this observation. [19][20][21] These and our findings demonstrate that GMF is not associated with a better prognosis than classic, nongranulomatous MF.…”
Section: Commentmentioning
confidence: 86%
“…The percentage of patients with unfavorable outcome is identical to that in the study by Chen et al, 13 who reported death due to the disease in 40% of patients with GMF. Whereas the occurrence of granulomas in MF has been considered to be associated with a favorable prognosis by some authors, 6,18 other investigators could not confirm this observation. [19][20][21] These and our findings demonstrate that GMF is not associated with a better prognosis than classic, nongranulomatous MF.…”
Section: Commentmentioning
confidence: 86%
“…The prognosis of GMF is still controversial 14 . Some authors suggest that the occurrence of granulomatous reaction in MF was considered to be associated with a favorable prognosis, in comparison with the nongranulomatous MF 3,19,20 . However, recent studies have showed that GMF was not associated with a better prognosis than nongranulomatous MF 6,16,21 .…”
Section: Discussionmentioning
confidence: 99%
“…9,12,14,15,18,19 Sézary and Lutzner cells or cells with cerebriform or damaged cell nuclei are common . 9,10,15,18,19 Granulomatous reactions have also been described in the Sézary syndrome. 20,21 In this case they are interpreted as individual inflammatory patterns without clinical or prognostic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in four cases there was evidence of concomitant sarcoidosis. 10,15,18,31 Although there is evidence for the frequent occurrence of malignant tumours, particularly within the framework of chronic active sarcoidosis, 2,32 a clear association for granulomatous mycosis fungoides has not been found.…”
Section: Discussionmentioning
confidence: 99%